New milleninnum intoduction to pakistan studies secondary , intermediate & gce o level - Rabbani, ikram .M (Caravan book house Pakistan, 2005)
New Millennium Introduction to Pakistan Studies offers a comprehensive overview of Pakistan's history, culture, politics, and geography, tailored for secondary, intermediate, and GCE O Level students.